2016
DOI: 10.1063/1.4954641
|View full text |Cite
|
Sign up to set email alerts
|

Torsional mode ultrasonic helical waveguide sensor for re-configurable temperature measurement

Abstract: This paper introduces an ultrasonic torsional mode based technique, configured in the form of a helical “spring-like” waveguide, for multi-level temperature measurement. The multiple sensing levels can be repositioned by stretching or collapsing the spring to provide simultaneous measurements at different desired spacing in a given area/volume. The transduction is performed using piezo-electric crystals that generate and receive T(0,1) mode in a pulse echo mode. The gage lengths and positions of measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In this work, an operational frequency range (150 -500 kHz) was chosen for experiments. Here, to ensure low dispersion, an appropriate thickness of the wire and suitable mean -helical and conical configurations due to curvature effect were considered for selection of waveguide dimensions using our earlier approaches [17][18][21][22][23] . Studies of waves in helical waveguides are reported in literature [25][26] with applications in civil structures.…”
Section: Ultrasonic Waves In Stepped-helical and Conical Waveguidesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, an operational frequency range (150 -500 kHz) was chosen for experiments. Here, to ensure low dispersion, an appropriate thickness of the wire and suitable mean -helical and conical configurations due to curvature effect were considered for selection of waveguide dimensions using our earlier approaches [17][18][21][22][23] . Studies of waves in helical waveguides are reported in literature [25][26] with applications in civil structures.…”
Section: Ultrasonic Waves In Stepped-helical and Conical Waveguidesmentioning
confidence: 99%
“…Different ultrasonic waveguide configurations have been reported by Periyannan and Balasubramaniam [16][17][18][19][20][21][22][23] for distributed temperature sensing. An ultrasonic system was developed for measuring the air temperature based on the phase shift records.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations